Fast-track Radioiodine Ablation Therapy After Thyroidectomy Reduces Sick Leave in Patients With Differentiated Thyroid Cancer (FASTHYNA Trial). (April 2019) - Waissi, Farahnaz; Kist, Jakob W.; Lodewijk, Lutske; de Wit, Ardine G.; van der Hage, Jos A.; van Dalen, Thijs; de Keizer, Bart; Valk, Gerlof D.; Borel Rinkes, Inne H. M.; Vriens, Menno R.
Abstract : Background: Recombinant human thyroid stimulating hormone (RhTSH) aided radioiodine ablative therapy (RIT) is current-day practice in the treatment of differentiated thyroid cancer (DTC). It is often planned 4 to 6 weeks after surgery or sometimes even longer (standard protocol). The RhTSH-aided RIT, however, has the advantage that it can be planned shortly after thyroidectomy. The FASTHYNA trial was designed to test the hypothesis that RIT 1 week after thyroidectomy (fast-track protocol) results in a significant reduction of sick leave with lower societal costs and with a better quality of life (QOL) compared with the current standard treatment. Methods: In a randomized, multicenter trial, we included patients with differentiated thyroid cancer, stage T1–3 N0–1 M0-x, who were treated with a total or completion thyroidectomy, with a paid job of at least 12 hours per week. The primary study end point was days of sick leave reported from time of surgery. Secondary end points were QOL and societal costs associated with absence from work. Results: Twenty patients were eligible for inclusion between November 2013 and May 2016. Significant decreases in mean duration of sick leave in the fast-track group versus the standard care group (115 and 280 hours, respectively, P = 0.02) and in costs associated with productivity losses ([Euro sign]4070.77 vs [Euro sign]9202.90, P = 0.02) were found. There were no significant differences in QOL between both groups. Conclusions: The trial showed a significant reduction in sick leave and in societal costs in the fast-track group without a deterioration of QOL. Therefore, fast-track ablation is desirable. Trial Registration: Netherlands trial register: NTR 3933.